Novel findings on anti-plaque effects of stannous fluoride - He, Tao; Zou, Yuanshu; DiGennaro, Joe; Biesbrock, Aaron R (American journal of dentistry, 2022)
To evaluate the antiplaque effects for 0.454% bioavailable gluconate chelated stannous fluoride (SnF₂) dentifrices versus controls by clinical model, plaque index, tooth surface and tooth type in a pooled analysis. Randomized controlled trials (RCTs) were conducted to evaluate plaque effects of SnF₂ dentifrices from the same formulation family over the past 30 years. Forty-four 4-day and longer-term (≥ 2 weeks) RCTs conducted in six countries with 3,336 subjects using Turesky Modified Quigley-Hein Plaque Index, Rustogi Modification of the Navy Plaque Index, Digital Plaque Imaging Analysis, and Silness and Löe Plaque Index were included. In 13 and 11 longer-term studies assessing SnF₂ dentifrice versus a negative or positive control, respectively, standardized differences in average plaque score of -1.15 (95% CI: -1.61, -0.69) and -0.74 (95% CI: -1.20, -0.28) were observed (P ≤ 0.011), favoring SnF₂. Reductions represented a 19% and 16% benefit versus the negative and positive control, respectively. In 18 and five 4-day studies assessing SnF₂ dentifrice versus a negative (NaF/SMFP) or positive (triclosan/chlorhexidine) control, respectively, differences in average 4-day plaque score of -0.27 (95% CI: -0.31, -0.23) and -0.15 (95% CI: -0.25, -0.06) were observed (P≤ 0.001) favoring SnF₂. Reductions represented a 14% and 11% benefit versus the negative and positive control, respectively. Significant antiplaque benefits for SnF₂ dentifrice were seen regardless of clinical model, plaque index, tooth surface or type, including brushed and unbrushed surfaces (P≤ 0.049). Bioavailable gluconate chelated SnF₂ dentifrices showed consistent plaque inhibition versus negative and positive controls across all conditions evaluated. Importantly, the effect on unbrushed surfaces illustrated the significant plaque inhibition benefit of SnF₂ beyond mechanical plaque removal.